Reconstruction of The State's Legal Responsibility in Protecting HajjPilgrimages Through Digital Governance Transformation AndStrengthening Extraterritorial Jurisdiction - Singgih Januratmo; Natsir Asnawi (Al-Makki Publisher, 2026)
The Hajj pilgrimage is a constitutional mandate that positions the state as the active guarantor of citizens’ rights, as stipulated in Article 29 paragraph (2) and Article 28I paragraph (4) of the 1945 Constitution. However, Law Number 8 of 2019 and its amendment through Law Number 14 of 2025 remain inadequate in addressing the complexities of pilgrim protection amid digital governance and cross-border jurisdictional dynamics. This research aims to analyze and reconstruct the state’s legal responsibility for implementing the Hajj pilgrimage in Indonesia in response to digital governance transformation and the complexities of extraterritorial jurisdiction. Considering the regulatory limitations of Law Number 8 of 2019 concerning the Implementation of the Hajj and Umrah Pilgrimages and its subsequent amendment through Law Number 14 of 2025 concerning Amendments to National Hajj Governance, this study employs a normative juridical method with legislative and conceptual approaches to examine the paradigm shift in state responsibility from an administrative model to rights-based protection encompassing physical, digital, and cross-border aspects. The results show that the digitalization of Hajj services and the integration of global systems have generated new legal implications, particularly regarding the protection of personal data as stipulated in Law Number 27 of 2022 concerning Personal Data Protection, as well as the expansion of state responsibility through the principles of state responsibility, extraterritorial obligation, and due diligence. Therefore, a reconstruction of legal norms is needed to address global challenges by strengthening extraterritorial jurisdiction, protecting digital sovereignty, establishing more effective, transparent, and accountable mechanisms of legal responsibility